2001
DOI: 10.1136/thorax.56.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the incidence, aetiology and outcome of adult lower respiratory tract illness in the community

Abstract: Background-Acute lower respiratory tract illness in previously well adults is usually labelled as acute bronchitis and treated with antibiotics without establishing the aetiology. Viral infection is thought to be the cause in most cases. We have investigated the incidence, aetiology, and outcome of this condition. Methods-Previously

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
224
2
31

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(265 citation statements)
references
References 21 publications
(19 reference statements)
8
224
2
31
Order By: Relevance
“…Several primary care studies have assessed the diagnostic value of signs and symptoms as individual items or in combination for diagnosing pneumonia [4,5], but there is limited data on the accuracy of GPs' clinical judgment, independent of a formal diagnostic model in lower respiratory tract infection (LRTI). MACFARLANE et al [1] found that GPs could not identify the need for antibiotic treatment with sufficient precision in patients with LRTI who had microbiological evidence of a bacterial infection. MELBYE et al [5] compared GPs' clinical diagnosis of pneumonia with findings on chest radiographs and found that GPs made a clinical diagnosis of pneumonia in only a minority of the patients who had a radiographic diagnosis of pneumonia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several primary care studies have assessed the diagnostic value of signs and symptoms as individual items or in combination for diagnosing pneumonia [4,5], but there is limited data on the accuracy of GPs' clinical judgment, independent of a formal diagnostic model in lower respiratory tract infection (LRTI). MACFARLANE et al [1] found that GPs could not identify the need for antibiotic treatment with sufficient precision in patients with LRTI who had microbiological evidence of a bacterial infection. MELBYE et al [5] compared GPs' clinical diagnosis of pneumonia with findings on chest radiographs and found that GPs made a clinical diagnosis of pneumonia in only a minority of the patients who had a radiographic diagnosis of pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients presenting with these symptoms in primary care are diagnosed as having acute bronchitis and a minority as having pneumonia. In general, pneumonia requires antibiotic treatment with close monitoring, while acute bronchitis is self-limiting and does not benefit meaningfully from antibiotic treatment [1][2][3]. General practitioners (GPs) usually have to either diagnose or exclude pneumonia on the basis of history, symptoms and signs alone, as it is neither feasible nor appropriate to perform chest radiographs in all patients presenting with acute cough or lower respiratory tract symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…3 These radiographs confi rm pneumonia in 5% to 19% and exclude pneumonia in most patients. 2,4,5 Imaging provides information relevant to the acute illness but may also reveal incidental fi ndings. [6][7][8][9] Such fi ndings can benefi t patients through earlier diagnosis and treatment, for example, in as yet undiagnosed heart failure or malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Prompt, accurate diagnosis of pneumonia in these patients is important to rule in the need for timely appropriate antibiotic treatment in some patients and to rule out the need for antibiotic treatment in others. Responsible general practitioners order chest radiographs in a minority of patients with acute cough.…”
Section: Introductionmentioning
confidence: 99%
“…2,3,4,5 International gibt es auffällig wenige Studien zu bakteriellen Erregern und deren Resistenzen, die aus einem allgemeinärztlichen Setting stammen. Dies mag teilweise damit erklärt werden, dass das Krankheitsbild im klinisch-stationären Bereich praktisch keine Relevanz hat und nur im Grenzbereich zur "community aquired pneumonia" -so z.B.…”
Section: Epidemiologie Der Erkrankung Und Der Erregerunclassified